Perbandingan Konsep Diri Anak Pendeta dan Anak Jemaat Gereja - Princen Princen; Mutiara Ezrani (Universitas Kristen Maranatha, 2021)
Children of clergy live in a complex and unique family context. They have different expectations from society compared to non-clergy children which results in a lot of internal pressures for them. Clergy children are expected to behave like what their parents teach in the church. Mistakes and failures they made are considered their parents’ mistakes and failures, and this also give them more pressure from their own family. All of these could lead the children of clergy to behave the opposites of what expected from them and might result in negative self-concept. The purpose of this study is to examine self-concept of both clergy and non-clergy children of adult age in Indonesia. Data was collected using Tennessee Self Concept Scale (TSCS) which were given online to 235 clergy and non-clergy children in Indonesia age 18-40 years old. Using Student’s T-test to analyze the data, the result revealed that there are no significant differences of self-concept between clergy and non-clergy children (t = 0,391; p > 0,05). Keywords: self-concept; clergy children; non-clergy children